The use of imaging tests to obtain optimal margins in breast surgery - Ostańska, Elżbieta; Bartusik-Aebisher, Dorota; Gustalik, Joanna; Aebisher, David; Galiniak, Sabina; Kaznowska, Ewa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Introduction. The proper negative margins (R0) breadth in the breast - conserving surgery for invasive breast cancer (IBC) and ductal carcinoma in situ (DCIS) is very important. The presence positive surgical margins (R1) is associated with the necessity of reoperation. It delays the adjuvant therapy and psychologically burdens the patient. The re-operation increases the costs of treatment. The introduction of mammography (MMG) increased detection of DCIS by 20%. With the increase in malignancy, cancer detection decreases in MMG, inversely in MRI groving. Effective preoperative and intraoperative diagnosis aims to reduce the number of R1 resections. Aim. The size of the tumor next to its biology, determines the clinical course of the tumor. The accurate analysis of imaging tests is important. Material and methods. This analysis was performed using a systematic literature search. Results. Adequate surgical margins in breast cancer surgery for breast cancer have been reviewed. It is important to know if the cancer is multifocal and what the extent of the tumor is. Conclusion. The adequacy of margins is important for adjusting the volume of excision. It is avoiding unnecessary resection of healthy breast tissue. It is essential for a good cosmetic result and the local recurrence rate. The combination of breast MRI with conventional breast imaging resulted in the lover rate of the R1 resectios and the lower rate of the re-operation.
Dorota Bartusik-Aebisher acknowledges support from the National Center of Science NCN (New drug delivery systems-MRI study, Grant OPUS-13 number 2017/25/B/ST4/02481).
Keywords: breast conserving surgery; ductal carcinoma in situ; extensive itraductal component; invasive breast cancer; lobular carcinoma in situ